Demonstration of viability and fertility and development of a molecular tool to identify YY supermales in a fish with both genotypic and environmental sex determination. Issue 15 (6th July 2018) - Hattori, Ricardo Shohei; Tashiro, Seiya; Zhang, Yan; Kakuta, Naoya; Yokota, Masashi; Strüssmann, Carlos Augusto; Yamamoto, Yoji
Abstract: The pejerrey possesses a genotypic sex determination system driven by the amhy gene and yet shows marked temperature‐dependent sex determination. Sex‐reversed XY females have been found in a naturally breeding population established in Lake Kasumigaura, Japan. These females could mate with normal XY males and generate YY "supermale" individuals that, if viable and fertile, would sire only genotypic male offspring. This study was conducted to verify the viability, gender, and fertility of YY pejerrey and to develop a molecular method for their identification. Production of YY fish was attempted by crossing a thermally sex‐reversed XY female and an XY male, and rearing the progeny until sexual maturation. To identify the presumable YY individuals, we first conducted a PCR analysis using amhy ‐specific primers to screen only amhy ‐positive (XY and YY) fish. This screening showed that 60.6% of the progeny was amhy ‐positive, which suggested the presence of YY fish. We then conducted a second screening by qPCR in order to identify the individuals with two amhy copies in their genome. This screening revealed 13 individuals, all males, with values twice higher than the other 30 amhy ‐positive fishes, suggesting they have a YY complement. This assumption as well as the viability, fertility, and "supermale" nature of these individuals was confirmed in progeny tests with XX females that yielded 100% amhy ‐positive offspring. These results demonstrate that qPCR can obviate progeny test as a means to identify the genotypic sex and therefore may be useful for the survey of all three possible genotypes in wild populations. Abstract : This study describes the establishment of a novel molecular tool for the identification of YY supermales, in addition to XX and XY genotypes, in pejerrey, a fish species with TSD and GSD. This tool will be instrumental to monitor the impacts of climate change on the genotypic and phenotypic sex ratios and consequent demographic processes in wild populations of this species, as shown in a preliminary screening of wild individuals.